Social identity in the energy transition: an analysis of the "Stop Adani Convoy" to explore social-political conflict in Australia. (August 2020) - Colvin, R.M.
Highlights: The social-political context of the energy transition in Australia is explored. The "Stop Adani Convoy" is explored as an episode of social-political conflict. From social psychology, the Social Identity Approach is applied. The Convoy fed into an "us" and "them" construction of the social-political context. Energy transitions need to centre local experience, values, and preferences. Abstract: Australia is undergoing an energy transition, largely spurred by efforts toward decarbonisation prompted by climate change. The energy transition, though, is socially and politically complex, particularly where the transition is felt most viscerally such as in resource-dependent regional communities. In this paper, I explore the social-political dimension of the energy transition in Australia by analysing a specific episode of social-political conflict: a multi-week, moving protest against a large thermal coal mine currently planned for development in Queensland, Australia, Adani Mining's Carmichael Coal Mine. The contestation was related to an 'Anti-Adani Convoy' that travelled from the southern-most state of Australia, Tasmania, to the regional Queensland community, Clermont, nearest the proposed mine site in mid-2019. The analysis is grounded in the social psychology tradition of the Social Identity Approach, and applies a model for exploring how social context makes salient certain identities and norms (the Situated Identity Enactment model). Social identity dimensions are explored via qualitative coding of online news media reporting on the Convoy, and from this analysis identity-based insights are drawn regarding the social-political dynamics of the energy transition in Australia. The Convoy experience indicates that regional communities are unlikely to be convinced about the need for the energy transition––or decarbonisation specifically and climate action more broadly––by advocates from afar who adopt tactics that appear as a threat to one group from another group. Instead, the energy transition will be best served by place-based, bottom-up initiatives that are congruent with local identity, values, preferences, and priorities.